Dynamical response of low-latitude middle atmosphere to major sudden stratospheric warming events - Sathishkumar, S.; Sridharan, S.; Jacobi, Ch. (My University, 2009)
The zonally averaged UK Meteorological Office (UKMO) zonal mean temperature and zonal winds for the latitudes 8.75°N and 60°N are used to investigate the low-latitude dynamical response to the high latitude sudden stratospheric warming (SSW) events that occurred during winter of the years 1998–1999, 2003–2004 and 2005–2006. The UKMO zonal mean zonal winds at 60°N show a short-term reversal to westward winds in the entire upper stratosphere and lower mesosphere and the low-latitude winds (8.75°N) show enhanced eastward flow in the upper stratosphere and strong westward flow in the lower mesosphere during the major SSW events at high latitudes. The mesosphere and lower thermosphere (MLT) zonal winds acquired by medium frequency (MF) radar at Tirunelveli (8.7°N, 77.8°E) show a change of wind direction from eastward to westward several days before the onset of SSW events and these winds decelerate and weak positive (eastward) winds prevail during the SSW events. The time variation of zonal winds over Tirunelveli is nearly similar to the one reported from high latitudes, except that the latter shows intense eastward winds during the SSW events. Besides, the comparison of daily mean meridional winds over Tirunelveli with those over Collm (52°N, 15°E) show that large equatorial winds are observed over Tirunelveli during the 2005–2006 event and over Collm during the 1998–1999 events. The variable response of MLT dynamics to different SSW events may be explained by the variability of gravity waves.
Keywords: Stratospheric warming; Middle atmosphere dynamics; Temperature; Winds; Sudden stratospheric warming; SSW